2018
DOI: 10.3126/jcmsn.v14i3.20733
|View full text |Cite
|
Sign up to set email alerts
|

Dental Age Estimation by Demirjian’s and Nolla’s Method in Children of Jorpati, Kathmandu

Abstract: Background: Growing individuals not only differ in the timing of the maturational events, but also in the sequence of these events. Age is one of the essential factors, which play an important role in every aspect of life like in clinical, medico-legal, forensic and anthropological applications and in planning treatment of   orthodontic and pedodontic patients. The aim of the study was to determine dental age from                       orthopantomogram using Demirjian’s method and Nolla’s method and to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
2
4
2
Order By: Relevance
“…Similar results were observed in a few studies done in selected Nepalese children population where Demirjian method was found to underestimate the age. 23,24,25 But the mean difference was very less in the present study compared to those other studies. 23,24,25 Thus, Demirjian's 7-teeth method was more applicable in the tested children.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Similar results were observed in a few studies done in selected Nepalese children population where Demirjian method was found to underestimate the age. 23,24,25 But the mean difference was very less in the present study compared to those other studies. 23,24,25 Thus, Demirjian's 7-teeth method was more applicable in the tested children.…”
Section: Resultscontrasting
confidence: 85%
“…23,24,25 But the mean difference was very less in the present study compared to those other studies. 23,24,25 Thus, Demirjian's 7-teeth method was more applicable in the tested children.…”
Section: Resultscontrasting
confidence: 85%
“…been stated in all of the published studies in Nepalese population. 14,16,19 Similarly underestimation in dental age was also observed in few other studies [21][22][23][24] while many studies using Demirjian method in several populations 2,4,6,9,13,25-28 have shown overestimation of dental age in contrast to our study. Internationally, using Demirjian method, an overestimation of dental age was found in Brazilians and Croats, 29 Malaysians, 30 Turks, 31 Bangladeshi and British, 32 Indians 2 and Spanish children.…”
Section: Resultssupporting
confidence: 82%
“…12 Nolla 5 age estimation method is based on the calcification of teeth and presents a high degree of intra-observer agreement (greater than 90%) but has been used only once in the Nepalese population. 13,14 The Willems 9 method, a modification of the Demirjian Dental age estimation and accuracy assessment by Demirjian, Nolla and Willems methods in Nepalese children for predicting the chronological age ABSTRACT method calculates dental age by direct scoring of tooth development which has provided comparatively smaller overestimations and precise estimation in some populations. 15 The major bias in age estimation is the differences in growth and development as well as other factors like hereditary, sex, nutrition, function and environment in different ethnic groups of population which must be taken into significant consideration while applying age estimation methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation